2020
DOI: 10.1530/joe-19-0102
|View full text |Cite
|
Sign up to set email alerts
|

Liver-expressed antimicrobial peptide 2 antagonizes the effect of ghrelin in rodents

Abstract: Ghrelin, a stomach-derived peptide, promotes feeding and growth hormone (GH) secretion. A recent study identified liver-expressed antimicrobial peptide 2 (LEAP2) as an endogenous inhibitor of ghrelin-induced GH secretion, but the effect of LEAP2 in the brain remained unknown. In this study, we showed that intracerebroventricular (i.c.v.) administration of LEAP2 to rats suppressed central ghrelin functions including Fos expression in the hypothalamic nuclei, promotion of food intake, blood glucose elevation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 38 publications
5
93
2
Order By: Relevance
“…A series of experimental results demonstrate that it weakens the binding ability of ghrelin to GHSR1a and reduces ghrelin-induced Ca( 2 + ) release in vitro [7,8,10]. Then, the physiological procedure of the LEAP2-GHSR1a interaction has been revealed in vitro [9,28]. Islam et al [28] found circulating leap2 levels change according to feeding status in rodent, while ghrelin downregulated hepatic leap2 expression via AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of experimental results demonstrate that it weakens the binding ability of ghrelin to GHSR1a and reduces ghrelin-induced Ca( 2 + ) release in vitro [7,8,10]. Then, the physiological procedure of the LEAP2-GHSR1a interaction has been revealed in vitro [9,28]. Islam et al [28] found circulating leap2 levels change according to feeding status in rodent, while ghrelin downregulated hepatic leap2 expression via AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the physiological procedure of the LEAP2-GHSR1a interaction has been revealed in vitro [9,28]. Islam et al [28] found circulating leap2 levels change according to feeding status in rodent, while ghrelin downregulated hepatic leap2 expression via AMPK pathway. Their results suggest a role of LEAP2 in the link between liver and stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the endogenous inverse agonist of GHSR1a has drawn attention to development of anti-obesity pharmacological agents. Systemic LEAP2 administration in mice suppresses only ghrelin-stimulated food intake and growth hormone release ( Ge et al, 2018 ), while in rats intraventricularly injected LEAP2 completely abolishes the central ghrelin effects (activation of the hypothalamic neurons, promotion of food intake, increase of blood glucose level, and body temperature reduction) but does not inhibit the central effects of DAG ( Islam et al, 2020 ). However, it is still unclear whether LEAP2 can cross the blood-brain-barrier similarly to ghrelin in order to affect GHSR1a in the central nervous system ( Abizaid and Hougland, 2020 ).…”
Section: Ghrelin Expression and Signalingmentioning
confidence: 99%
“…A large number of studies have revealed that ghrelin also regulates the immune system by acting on immune cells and endothelial cells to suppress the production of pro‐inflammatory cytokines, suggesting its therapeutic viability in inflammatory conditions (Colldén et al., 2017; Yanagi et al., 2018). Leap2 was found to be highly expressed in the liver and intestine in rodents, and its expression was decreased in the liver of rats under fasting condition (Islam et al., 2020). LEAP2 was also demonstrated to act as an inverse agonist of GHSR1a by blocking its constitutive activity (M’Kadmi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although GHSR1a is widely expressed in the central nervous system (CNS) (Al‐Massadi et al., 2018), it is still unclear whether LEAP2 is involved in human neurological diseases. We demonstrated that the intracerebroventricular administration of LEAP2 to rats antagonized central ghrelin functions, including the promotion of food intake, elevation of blood glucose levels, and reduction of body temperature (Islam et al., 2020). Previous studies have not shown whether LEAP2 is present in human cerebrospinal fluid (CSF), and if so, whether its levels are altered in neurological disorders.…”
Section: Introductionmentioning
confidence: 99%